A Review Article : Ethanol Fermentation by Saccharomyces cerevisiae using Agricultural Waste - Maftukhah, siti; Amyranti, Mutia (UNISTEK, 2020)
Bioethanol is one of the most promising and eco-friendly alternatives to fossil fuels, which is produced from renewable sources. Bioethanol can be produced from different kinds of raw materials. Conventional crops such as corn and sugarcane are unable to meet the global demand of bioethanol production due to their primary value of food and feed. Agricultural wastes are cost effective, renewable and abundant. To do this, very high gravity (VHG) fermentation which involves use of medium containing high sugar concentration(>250g/L) must be implemented to achieve high ethanol concentration. However, VHG fermentation leads to significant stress for Saccharomyces cerevisiae due to osmotic pressure at the beginning of the fermentation and high ethanol content at the end. At this review, rice straw is the most abundant waste compared to the other major wastes and potentially produce 205 billion liters bioethanol per year, which is the highest among these four mentioned agricultural wastes.